2018
DOI: 10.1111/jai.13659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormones on vertebral numbers in two cyprinid fish species:Rutilus rutilus(Linnaeus, 1758) andAbramis brama(Linnaeus, 1758)

Abstract: Summary Previous studies revealed that thyroid hormones (TH) are crucial regulators of fish development and that manipulation of the thyroid gland function can induce developmental heterochronies. These heterochronies are known to be responsible for changes in the number of serially repeating skeletal elements, such as scales, fin rays and pharyngeal teeth. The present study demonstrates that thyroid function manipulation provokes heterochronies in the development of the fish axial skeleton. We studied the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Embryonic differentiation/organogenesis and growth in teleosts is regulated by THs, likely by triggering both GH [e.g., THs increase GH mRNA transcription in rainbow trout ( 144 ) and carp ( 145 ), and increase synthesis and release in hybrid tilapia ( 146 )] and IGF-I [e.g., THs induce in vivo and in vitro synthesis/release in Mozambique tilapia ( Oreochromis mossambicus ) ( 147 )]. Since THs are crucial regulators of growth ( 148 , 149 ), inhibition of thyroid function results in impairment in the development of brain, skeleton, and other organs, as well as in pigmentation. For example, in zebrafish, treatment with T 3 increases IGF-1 expression and enhances swim bladder and eye development but IGF-1 receptor blockade suppresses these effects of T 3 on swim bladder and eye ( 150 ).…”
Section: Role Of the Thyroid Axis On Somatic Development And Growthmentioning
confidence: 99%
“…Embryonic differentiation/organogenesis and growth in teleosts is regulated by THs, likely by triggering both GH [e.g., THs increase GH mRNA transcription in rainbow trout ( 144 ) and carp ( 145 ), and increase synthesis and release in hybrid tilapia ( 146 )] and IGF-I [e.g., THs induce in vivo and in vitro synthesis/release in Mozambique tilapia ( Oreochromis mossambicus ) ( 147 )]. Since THs are crucial regulators of growth ( 148 , 149 ), inhibition of thyroid function results in impairment in the development of brain, skeleton, and other organs, as well as in pigmentation. For example, in zebrafish, treatment with T 3 increases IGF-1 expression and enhances swim bladder and eye development but IGF-1 receptor blockade suppresses these effects of T 3 on swim bladder and eye ( 150 ).…”
Section: Role Of the Thyroid Axis On Somatic Development And Growthmentioning
confidence: 99%
“…Variations in the number of vertebrae are prevalent within and among fish species. The vertebral counts are determined by geographic distribution [57], living environment [58], hormone levels [28], and expression levels of related genes [59], but some research indicates that most fish have a fixed number of vertebrae during early ontogeny [57,60]. In this study, mstnb knockout yellow catfish were found to have decreased centrum counts.…”
Section: Discussionmentioning
confidence: 65%
“…Skeletal examination of juvenile specimens (5-10 cm) was performed by making the skeletal specimens transparent and staining with them Alizarin red (Aladdin, Shanghai, China) and Alcian blue (Aladdin, Shanghai, China) to identify bone and cartilage, using the methods described in references [25][26][27][28]. They were prepared by removing the skin, gills, and viscera.…”
Section: Skeletal Staining and Vertebral Countsmentioning
confidence: 99%
“…This phenomenon is explained by the morphogenetic influence of the caudal complex, whose normal development includes several vertebral fusions [ 128 ]. The increased frequency of abnormalities in the caudal region was also detected as a result of thyroid hormone disruption [ 129 , 130 ]. However, in the deformed (SH) barbs, the frequency of deformed vertebrae was lower in the last caudal vertebrae ( Fig 8 ).…”
Section: Discussionmentioning
confidence: 99%